Determinan Pengangguran Lulusan SMA di Provinsi Sumatera Utara Tahun 2019 - Viki Tria Zianrini; Efri Diah Utami (Politeknik Statistika STIS, 2021)
Unemployment is one of the most common problems in developing countries. In Indonesia, unemployment is dominated by a highly educated workforce or educated unemployed. Educated unemployment is the workforce with a minimum of high school education and is not working. Based on BPS data in 2019, the population aged 15 years and over who are included in open unemployment according to the highest education completed are those with the latest high school education, reaching 1,994,836 people. North Sumatra province occupies the first position with the highest number of educated unemployed high school graduates when compared to other provinces in Sumatra, namely there were 130,103 unemployed high school graduates in 2019. Using secondary data from the August 2019 National Labor Force Survey, this study aims to determine the variables -variables that affect the unemployment status of high school graduates in North Sumatra in 2019. The analytical method used is binary logistic regression. The results showed that the variables that significantly affected the unemployed status of high school graduates were age, area of residence, marital status, and status in the household. For high school graduates who are young, live in urban areas, are not the head of the household, and are not married, they have a greater tendency to be unemployed.